2021
DOI: 10.1089/aid.2021.0012
|View full text |Cite
|
Sign up to set email alerts
|

Progression Risk in People with HIV and COVID-19: Predictive Performance of Current Risk Scores

Abstract: People with HIV (PWH) might have a higher risk of adverse coronavirus disease 2019 (COVID-19) outcomes. Several scores were developed to predict COVID-19 progression to critical disease and are often used among PWH. We assessed the performance of two commonly used risk equations among PWH and COVID-19. Participants were identified from a multicenter cohort of 6,361 PWH on regular follow-up at 2 university hospitals. Of 99 HIV-infected individuals with confirmed SARS-CoV-2 infection, 63 had complete data and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Some of the published studies had limitations such as small sample sizes or variable periods over the course of the pandemic. Some studies have reported no difference among those living with and without HIV in the frequency of SARS-CoV-2 test positivity 7 or in the frequency of poor outcomes, [8][9][10][11][12] including mortality, 8,9,13 particularly when HIV is well-controlled. Others have reported that severe illness 2,14 and mortality 1,4,5,15,16 due to COVID-19 are higher among PWH compared with those without HIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the published studies had limitations such as small sample sizes or variable periods over the course of the pandemic. Some studies have reported no difference among those living with and without HIV in the frequency of SARS-CoV-2 test positivity 7 or in the frequency of poor outcomes, [8][9][10][11][12] including mortality, 8,9,13 particularly when HIV is well-controlled. Others have reported that severe illness 2,14 and mortality 1,4,5,15,16 due to COVID-19 are higher among PWH compared with those without HIV infection.…”
Section: Introductionmentioning
confidence: 99%